(untitled) (Scientific journal of the Fergana State University, 2023)
Up to date the scientific research in the area of onomastics in whole and in Uzbek anthroponymy in particular, was reduced to full statistical systematization of names. As for theoretical aspects of antroponymy there arise investigations which do not separate cover all the completeness of the problem yet.